Insight investigation of the on-site activated sludge reduction induced by metabolic uncoupler: Effects of 2, 6-dichlorophenol on soluble microbial products, microbial activity, and environmental impact. (January 2022) - Lin, QingYuan; Zhang, Jun; Yin, Linlin; Zuo, Wei; Li, Lipin; Tian, Yu
Abstract: Metabolic uncoupling technology was one of the methods widely used to on-site control the production of excess sludge in wastewater treatment processes. However, the uncoupler effects on soluble microbial products (SMP), microbial activity, and environment impact have few been reported. This study showed that sludge yield was reduced by 33.3% at 2, 6-dichlorophenol (2, 6-DCP) concentrations of 10 mg/L. The addition of 2, 6-DCP also reduced the content of polysaccharide and protein in SMP, and the three-dimension excitation emission matrix (3D-EEM) suggested that the fluorescence intensities of humic acid-like, fulvic acid-like, and tryptophan protein-like substances decreased, proving that 2, 6-DCP addition will weaken the interaction between microorganisms and the environmental matrix. Moreover, 2, 6-DCP addition will change the microbial morphology and community of activated sludge. The active or respiring bacteria portion was lessened, and sludge flocs become dispersed, but it will not affect its settling performance. Surprisingly, 2, 6-DCP has certain biodegradability and could be used as an environmentally friendly metabolic uncoupler under low-concentration dosing conditions. This study systematically evaluated the effect of 2, 6-DCP on sludge production, SMP contents, microbial morphology, microbial community, demonstrating the environmental impact and application feasibility in the wastewater treatment systems. Graphical abstract: Image 1 Highlights: Dosing 2, 6-DCP reduces the SMP contents of activated sludge. The sludge flocs became dispersed after adding 2, 6-DCP. The addition of 2, 6-DCP changed the abundance of bacteria in the system. The 2, 6-DCP concentration lower than 10 mg/L has little impact on the environment.